Investigação de moléculas híbridas para o tratamento anticâncer - Costa, Felipe Ribaldo Ferreira da (Universidade Federal de São Carlos, 2022)
Cancer is the attribution given to the uncontrolled growth and proliferation of abnormal cells capable of invading and destroying the adjacent tissue. According to the World Health Organization (WHO), the global growth in cancer cases will reach the 60% mark by 2040, totaling around 37 million cases. In Brazil, estimates released by the National Cancer Institute (INCA) project that approximately 66 thousand new individuals will be affected by prostate cancer (PC) in 2022. In the case of the metastatic and hormone-refractory type (mHRPC), the cells are not responsive to conventional treatment. In order to circumvent this situation, the use of cytotoxic therapies targeting microtubules (MTs) is a well-established option in clinical practice. MTs are structural elements constituted by the dimeric protein tubulin, which performs cellular functions through its intrinsic capacity for dynamic instability: polymerization and depolymerization. Changes in this dynamic lead to blockage of mitosis and cell migration, directing the cell to apoptosis. This behavior can be induced by the use of modulating agents in known sites of tubulin, configuring a promising conduct when it comes to the development of antitumor drugs. In this context, the union of pharmacophoric groups to generate hybrid molecules emerges as an innovative alternative. Thus, the present work brings results regarding the in vitro screening of bioactive ligands for the treatment of mHRPC. A cell line of PC (DU-145) and three non-tumor ones [human (HFF-1) and murine (FC3H) fibroblasts, and human prostate epithelial cells (RWPE-1)] were submitted to cell viability assays to evaluate the potency of 10 quinazoline-chalcone hybrids (AQCs) from their IC50 and CC50 values. For the selected samples, these values were used to determine the selectivity index (SI). Three hybrids (AQC-02, AQC-04 and AQC-08) were active in the PC cell line (IC50 ≤ 20 µM) and selective against non-tumor ones (SI ≥ 5), and therefore referred to cellular assays involving analysis of characteristics observed in the metastatic cascade. The 3 hybrids inhibited migration in qualitative wound healing assays at single concentration (≥ 50%) and concentration x effect. Furthermore, through a transwell study based on Boyden's chamber, it was possible to quantify and confirm the inhibitory effect of hybrids on tumor cell migration and invasion (both with IC50 ≤ 10 µM). Kinetic assays directed to the molecular target corroborated the classification of the hybrids as tubulin polymerization inhibitors, as well as made it possible to determine their IC50 values (5.71 ± 0.09; 9.04 ± 0.40 and 8.40 ± 0.31 µM, respectively). Competition assays suggested that the hybrids possibly interact with tubulin near or at the colchicine site itself. Additionally, fluorescence assays reinforced the action of the compounds in destabilizing cell division and promoting the nuclear fragmentation of DU-145. This work, therefore, shows promising results that, in consonance, support the identification of lead compounds eligible for in vitro and in vivo ADME (Absorption, Distribution, Metabolism and Excretion) assays, aiming at the selection of candidates for new drugs for the mHRPC chemotherapy.
Investigation of hybrid molecules for cancer treatment
Keywords: Câncer de próstata; Química medicinal; Descoberta e desenvolvimento de fármacos; Tubulina; Agentes direcionados aos microtúbulos; Moléculas híbridas; Quinazolina; Chalcona; Prostate cancer; Medicinal chemistry; Drug discovery and development; Tubulin; Microtubule-targeting agents; Hybrid molecules; Quinazoline; Chalcone; CIENCIAS BIOLOGICAS::BIOFISICA::BIOFISICA CELULAR; CIENCIAS BIOLOGICAS::BIOFISICA::BIOFISICA MOLECULAR; CIENCIAS BIOLOGICAS::FARMACOLOGIA